An economic study of soybean marketing (Glycine max) in Bundi district of Rajasthan - Meena, Chiranjee Lal; Singh, D.P.; Singh, Hemendra (Annals of Agricultural Research, 2014)
Soybean is a major oilseed crop of Rajasthan The multi-stage random sampling method was used for present study in Bundi district. The analysis of net share revealed that channel II was more remunerative because farmer’s share in consumer rupee was highest (70.33 per cent). The net share of commission agent was involved only in channel IV. It has 0.85 per cent share in consumer rupee. The net share of wholesaler was higher in channel I (3.59 per cent), ITC (3.84 per cent) in channel II and Tilam Sangh (6.80 per cent) in channel III, (6.04 per cent) in channel IV respectively). The net share of miller was highest 12.54 per cent in channel I. Price spread was maximum in channel I (32.90 per cent) followed by channel IV (30.31 per cent), channel I (31.16 per cent), and channel II (29.66 per cent). The high fluctuation in price was reported as the main constraint in marketing of soybean by small (93 per cent), medium (83 per cent) and large farmers (42 per cent). The delay in payment of produce on its sale was highlighted by small farms (60 per cent) followed by medium farmers (58 per cent) and large farmers (50 per cent). Small farmers (61 per cent) highlighted poor transportation facility followed by medium farmers (42 per cent) and large farmers (33 per cent). The study suggested that there should be control on price fluctuation of produce and government should increase cooperative marketing and technological changes in the study area.